An update on gout for primary care providers. Issue 4 (17th April 2016) - Harding, Mariann
Abstract : Abstract: This article discusses the current beliefs regarding the pathogenesis of gout and reviews the 2012 guidelines from the American College of Rheumatology regarding diagnostic testing, optimal treatments, and lifestyle modifications. Implementing these guidelines will assist clinicians in resolving acute episodes and managing gout long term, improving outcomes and quality of life. Abstract : This article discusses the current beliefs regarding the pathogenesis of gout and reviews the 2012 guidelines from the American College of Rheumatology regarding diagnostic testing, optimal treatments, and lifestyle modifications. Implementing these guidelines will help clinicians resolve acute episodes and manage gout, improving outcomes and quality of life.